Development and Validation of a Capacitor–Current Circuit Model for Evaporation-Induced Electricity - Wenluan Zhang; Runru Tristan Liu; Yumin Huang (Applied Sciences)
Evaporation-induced electricity is a promising approach for sustainable energy generation which is particularly suited for off-grid and Internet-of-Things (IoT) applications. Despite significant progress, the mechanism of electricity generation remains debated due to complex factors. In this study, we introduce a simplified capacitor–current circuit model to describe the behavior of evaporation-induced electricity. The primary objective of this work is to provide a framework for understanding the transient and steady-state behavior of this phenomenon. We validated this model using experimental data from wood-based nanogenerators with citric acid modified microchannels. The fitting results revealed a steady-state current of approximately 9.832 μA and an initial peak current of 16.168 μA with a time constant of 621.395 s. These findings were explained by a hybrid model incorporating a capacitor and current source components, and subsequent discharge through internal resistance. This simplified model paves the way for better understanding and optimization of evaporation-induced electricity, highlighting potential improvements in device design for enhanced performance. While improving device performance is beyond the scope of this study, the insights gained from this model offer a foundation for future optimization and the enhanced performance of evaporation-induced electricity generation devices.